Efecto de physalis peruviana sobre la lipoperoxidación inducida en mucosa gástrica de rattus norvegicus var. albinus ovariectomizadas - Olano Leiva, Alicia Anais (2015)
This study aims to determine the effect of Physalis peruviana (Aguaymanto) on lipid peroxidation induced gastric mucosa of Rattus norvegicus var. Albinus ovariectomized (OVX). Experimental animals were divided into four groups: OVX control, standard OVX and OVX problems. The specimens were treated with balanced diet for the control OVX group was treated with physiological saline 0.9%, the pattern OVX group was given 0.4 mg/Kg p.c fluoxetine 20 mg and group problem 1 OVX crude extract was administered Physalis peruviana 3.0 g / kg previously induced with fluoxetine for 21 days after two months of surgery and the last Problem 2 OVX group was administered the crude extract of Physalis peruviana 4.5 g / kg body weight previously induced with fluoxetine for 21 days starting 2 weeks surgery. At the end lipoperoxidation was determined as a marker having malondialdehyde, which in the presence thiobarbituric acid facilitates reading spectrophotometrically at 532 nm wavelength. It is concluded that treatment with different doses in dose Physalis peruviana 3.0 g / kg and 4.5 g / kg showed a protective effect both in levels of MDH on the gastric mucosa of Rattus norvegicus var. Albinus OVX as its statistical significance by Tukey test with a value of 95% (p> 0.05).